DEVELOPING INTERACTIVE AUDIO-LEARNING MATERIALS TO TEACH SPEAKING SKILLS - A'yun Latifah Hanum; Widiarini Widiarini; Siti Rofi'ah (PROJECT (Professional Journal of English Education), 2023)
As a research design, this research utilizes Borg and Gall's Research and Development research technique, with the objective of developing instructional audio media as a method for creating interactive audio teaching materials for mastering speaking abilities. To pursue the study's aims, unstructured interviews and questionnaires were used to collect perspectives from teachers and thirty-four junior high school students. This study combines several methods of teaching speaking and listening skills with interactive audio learning material that are integrated with the Spotify application. The validation result of the media expert is 80%, and the validation result of the content expert is 67%, the validity result used SPSS is 0.3338, and the reliability statistic Cronbach's Alpha is 0.754. This result resulted in the conclusion that this learning media was valid, interesting, and appropriate. It was determined that speaking instructional materials can be used in the learning process. The designed training instruments can increase students' speaking abilities. Teachers use this product as an alternative method for learning English, — especially for speaking abilities. Keywords:  Audio-Learning; Speaking Skills